2009
DOI: 10.1186/1471-2202-10-110
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cerebrospinal fluid production by caffeine consumption

Abstract: Background: Caffeine is the most commonly consumed psycho-stimulant in the world. The effects of caffeine on the body have been extensively studied; however, its effect on the structure of the brain has not been investigated to date.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
53
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 38 publications
(48 reference statements)
3
53
0
3
Order By: Relevance
“…Acute administration of ethanol reduced CSF production by about 40% whereas alcoholic humans present enlarged cerebral ventricles (potentially consistent with an increase in CSF production due to chronic ethanol exposure) (Javaheri and Corbett, 1998). A similar effect on CSF production has been observed with caffeine (Han et al, 2009;Wostyn et al, 2011). This 'effect inversion' of caffeine may be secondary to the modulation of the expression of Na + -K + -ATPase in the choroid plexuses by adenosine receptors (Han et al, 2009).…”
Section: Tablementioning
confidence: 61%
See 1 more Smart Citation
“…Acute administration of ethanol reduced CSF production by about 40% whereas alcoholic humans present enlarged cerebral ventricles (potentially consistent with an increase in CSF production due to chronic ethanol exposure) (Javaheri and Corbett, 1998). A similar effect on CSF production has been observed with caffeine (Han et al, 2009;Wostyn et al, 2011). This 'effect inversion' of caffeine may be secondary to the modulation of the expression of Na + -K + -ATPase in the choroid plexuses by adenosine receptors (Han et al, 2009).…”
Section: Tablementioning
confidence: 61%
“…A similar effect on CSF production has been observed with caffeine (Han et al, 2009;Wostyn et al, 2011). This 'effect inversion' of caffeine may be secondary to the modulation of the expression of Na + -K + -ATPase in the choroid plexuses by adenosine receptors (Han et al, 2009). Puscas et al (1999) demonstrated that omeprazole has the ability to inhibit carbonic anhydrases I, II and IV.…”
Section: Tablementioning
confidence: 66%
“…In the present study, therefore, adult MPS IIIA mice were administered with 10 µl of therapeutic lentivirus into each lateral ventricle, at an infusion rate of 0.25 µl/min. Currently, were are unaware of any other studies reporting the delivery of similarly large volumes to the brains of adult mice; however, we estimate that this dose would have increased the rate of flow of fluid the brain's circulatory systems needed to deal with by approximately 75%, which we considered to be tolerable considering that caffeine and forskolin can increase CSF production by 60% and 100%, respectively, without deleterious effects . This is because resorption of the CSF, mostly via the arachnoid granulations and villi, increases in response, and thereby normal intracranial pressure is maintained .…”
Section: Discussionmentioning
confidence: 97%
“…Caffeine also decreases the ratio of CBF:CMRO 2 (cerebral blood flow to cerebral metabolic rate for oxygen) (Chen and Parrish, 2009). Many recent studies have investigated the effect of caffeine on BOLD responses (blood oxygen dependent MRI) (Rack-Gomer et al, 2009) and functional MRI responses and CBF changes (Haase et al, 2005;Sigmon et al, 2009), and one animal study has suggested an effect on cerebrospinal fluid formation (Han et al, 2009). All these documented actions are theoretically beneficial for the high altitude brain, since vasodilation and overperfusion would be minimized without sacrificing oxygenation and metabolism.…”
Section: Does Caffeine Depress Ventilation?mentioning
confidence: 96%